2016
DOI: 10.1002/hep.28712
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X receptor activation increases reverse cholesterol transport by modulating bile acid composition and cholesterol absorption in mice

Abstract: Activation of farnesoid X receptor (FXR) markedly attenuates the development of atherosclerosis in animal models. However, the underlying mechanism is not well elucidated. Here we show that the FXR agonist obeticholic acid (OCA) increases fecal cholesterol excretion and macrophage reverse cholesterol transport (RCT) dependent on activation of hepatic FXR. OCA does not increase biliary cholesterol secretion but inhibits intestinal cholesterol absorption. OCA markedly inhibits hepatic cholesterol 7α-hydroxylase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 48 publications
(107 reference statements)
6
84
1
Order By: Relevance
“…Furthermore, the observations by Van der Velde et al are in contrast to those by De Boer et al who showed that using bile diverted rats that induction of TICE by intestinal FXR activation required a change of biliary bile acid composition towards a more hydrophilic profile (22). This is in line with another murine study using different FXR agonists and an earlier in vitro observation where UDCA was more efficient in promoting ABCG5/8 dependent cholesterol efflux than CA (47,48).…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, the observations by Van der Velde et al are in contrast to those by De Boer et al who showed that using bile diverted rats that induction of TICE by intestinal FXR activation required a change of biliary bile acid composition towards a more hydrophilic profile (22). This is in line with another murine study using different FXR agonists and an earlier in vitro observation where UDCA was more efficient in promoting ABCG5/8 dependent cholesterol efflux than CA (47,48).…”
Section: Discussionmentioning
confidence: 61%
“…OCA is known to inhibit bile acid synthesis and decrease the bile acid pool (28). INT-777 did not affect bile acid synthesis and pool size (22), whereas the effect of INT-767 on bile acid synthesis has not been studied.…”
Section: Differential Effects Of Int-767 Oca and Int-777 On Hepaticmentioning
confidence: 97%
“…Treatment with obeticholic acid results in decreases in alkaline phosphatase, γ-glutamyl transpeptidase and alanine aminotransferase in PBC patients (108, 109). The anti-inflammtory effects of obeticholic acid in PBC patients are likely related to FXR mediated inhibition of cholesterol 7α-hydroxylase (CYP7A1) and a reduction in the bile acid pool (110). …”
Section: Bile Acids As Therapeutics For Liver Diseasesmentioning
confidence: 99%